Evaluation of a competitive ELISA for antibody detection against avian influenza virus - Song, D.S., Green Cross Veterinary Priducts, Youngin, Republic of Korea; Lee, Y.J., National Veterinary Research and Quarantine Service, Anyang, Republic of Korea; Jeong, O.M., National Veterinary Research and Quarantine Service, Anyang, Republic of Korea; Kim, Y.J., National Veterinary Research and Quarantine Service, Anyang, Republic of Korea; Park, C.H., Animal Genetics, Suwon, Republic of Korea; Yoo, J.E., Animal Genetics, Suwon, Republic of Korea; Jeon, W.J., National Veterinary Research and Quarantine Service, Anyang, Republic of Korea; Kwon, J.H., National Veterinary Research and Quarantine Service, Anyang, Republic of Korea; Ha, G.W., Animal Genetics, Suwon, Republic of Korea; Kang, B.K., Green Cross Veterinary Priducts, Youngin, Republic of Korea; Lee, C.S., Green Cross Veterinary Priducts, Youngin, Republic of Korea; Kim, H.K., Seoul National University, Seoul, Republic of Korea; et al. (Journal of veterinary science (Suwŏn-si, Korea), 2009)
Active serologic surveillance is necessary to control the spread of the avian influenza virus (AIV). In this study, we evaluated a commercially-available cELISA in terms of its ability to detect AIV antibodies in the sera of 3,358 animals from twelve species. cELISA detected antibodies against reference H1- through H15-subtype AIV strains without cross reactivity. Furthermore, the cELISA was able to detect antibodies produced following a challenge of the AIV H9N2 subtype in chickens, or following vaccination of the AIV H9 or H5 subtypes in chickens, ducks and geese. Next, we tested the sensitivity and specificity of the cELISA with sera from twelve different animal species, and compared these results with those obtained by the hemagglutination-inhibition (HI) test, the "gold standard" in AIV sera surveillance, a second commercially-available cELISA (IZS ELISA), or the agar gel precipitation (AGP) test. Compared with the HI test, the sensitivities and specificities of cELISA were 95% and 96% in chicken, 86% and 88% in duck, 97% and 100% in turkey, 100% and 87% in goose, and 91% and 97% in swine, respectively. The sensitivities and specificities of the cELISA in this study were higher than those of IZS ELISA for the duck, turkey, goose, and grey partridge sera samples. The results of AGP test against duck and turkey sera also showed significant correlation with the results of cELISA (R-value greater than 0.9). In terms of flock sensitivity, the cELISA correlated better with the HI test than with commercially-available indirect ELISAs, with 100% flock sensitivity.